STUCK IN LA PROSPERIDAD: MADRID'S METAMORPHOSIS FROM DICTATORSHIP TO DEMOCRACY IN JUAN JOSÉ MILLÁS'S LA SOLEDAD ERA ESTO. - Phillips, Nick (Hispanófila)
The article discusses the transformation of Madrid, Spain from a dictator to democratic country in 1980s-90s through the lens of Spanish writer Juan Jose Millas, who wrote several novels like El desorden de tu nombre. Topics discussed include feminine perspective of self-transformation, neighborhood's identity as a peripheral community serving as a destination for immigrants and increase in economic and social mobility in a democracy.